Munāẓarah Literature in Urdu: An Extra-Curricular Educational Input in Pakistan’s Religious Education - Rahman, Tariq; Rahman, Tariq (Islamic Studies, 2008)
This article looks at the institution of debate, the munāẓarah, in the religious education sector of Pakistan. It argues that the munāẓarah occupies an important position in madrasah education and the ’ulamā’ create their identity around a core of differences from other sects, sub-sects and heretical or alien beliefs which are brought out in the open in munāẓarahs. Moreover, certain books and pamphlets embodying the form of argumentation and other features of the munāẓarah are part of the informal, extra-curricular reading material both of madrasah students and teachers as well as religious people outside it. This kind of literature emphasizes differences and, therefore, presumably predisposes those who are exposed to it to intolerance of the ’other’. However, the solution of this problem is not to ban such literature but to reduce Muslim anger and change government policies in the direction of avoiding violence.